2003
DOI: 10.4049/jimmunol.171.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant TCR Ligand Induces Tolerance to Myelin Oligodendrocyte Glycoprotein 35-55 Peptide and Reverses Clinical and Histological Signs of Chronic Experimental Autoimmune Encephalomyelitis in HLA-DR2 Transgenic Mice

Abstract: In a previous study, we demonstrated that myelin oligodendrocyte glycoprotein (MOG)-35-55 peptide could induce severe chronic experimental autoimmune encephalomyelitis (EAE) in HLA-DR2+ transgenic mice lacking all mouse MHC class II genes. We used this model to evaluate clinical efficacy and mechanism of action of a novel recombinant TCR ligand (RTL) comprised of the α1 and β1 domains of DR2 (DRB1*1501) covalently linked to the encephalitogenic MOG-35-55 peptide (VG312). We found that the MOG/DR2 VG312 RTL cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 36 publications
6
103
2
Order By: Relevance
“…Moreover, the cumulative disease index that monitors the severity of the disease throughout the course of disease showed that there was a significant difference between RTL2001MII treated group vs the control group (data not shown). These results strongly suggest that only the cognate peptide/MHC complex but not the MHC moiety alone could modulate arthritogenic T cell responses, consistent with our previous studies (40,41,44).…”
Section: Rtl2001mii Treatment Reduced the Incidence And Clinical Signsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, the cumulative disease index that monitors the severity of the disease throughout the course of disease showed that there was a significant difference between RTL2001MII treated group vs the control group (data not shown). These results strongly suggest that only the cognate peptide/MHC complex but not the MHC moiety alone could modulate arthritogenic T cell responses, consistent with our previous studies (40,41,44).…”
Section: Rtl2001mii Treatment Reduced the Incidence And Clinical Signsupporting
confidence: 81%
“…In our previous studies, we demonstrated that both monomeric DR2-derived and I-A s -derived RTLs could protect and treat the clinical and histological signs of EAE in DR2 Tg mice (39,41) and SJL mice (40), respectively. In the current study, we used a similar approach, constructing monomeric I-A q -derived RTLs covalently linked with bCII257-270 peptide (RTL2001) (US patent no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WNV T-cell ligand sequences were identified by use of HLA transgenic mice, a leading animal model system for analysis of HLA-restricted T-cell responses to human pathogens (4,12,25,40,41,43,49,63,65), as follows: H-2 class II deficient, HLA-DR2 (DRB1*1501) (68), HLA-DR3 (DRB1*0301) (29,64), and HLA-DR4 (DRB1*0401)/human CD4 (huCD4) (6,10); and H-2 class I deficient, HLA-A2.1 (A*0201) (HHD monochain) (44), HLA-A24 (A*2402)/huCD8␣ (F. Lemonnier unpublished data), and HLA-B7 (B*0702) (51). HLA-DR2 transgenic mice express chimeric molecules, with ␣1 and ␤1 domains encoded by the HLA-DRA1*0101 and -DRB1*1501 sequences and the other domains encoded by I-E␣ and I-E␤ sequences from the I-E promoters (68). HLA-DR3 transgenic mice express the full-length HLA-DRA1*0101 and -DRB1*0301 sequences (29,64).…”
Section: Methodsmentioning
confidence: 99%
“…HLA-DR2b transgenic mice bearing chimeric MHC class II molecules consisting of the a1 and h1 sequences of HLA-DRA1*0101 and HLA-DRB1*1501 and the a2 and h2 domains of IEa and IEb, respectively, were developed as previously described (12,13 [171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190] presented by autologous DC. CD4 T-cell lines were generated from PBMC of granulomatous prostatitis patients by multiple stimulations with peptide PSA [171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190] in the presence of irradiated autologous PBMC.…”
Section: Methodsmentioning
confidence: 99%